Botswana : Technical Assistance Report-Report on the National Accounts Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses results of a technical assistance report prepared to assist Statistics Botswana (SB) improve the quality of the national accounts statistics. SB is currently rebasing the annual national accounts with an expected release date of March 2020. SB is currently rebasing the national accounts to a base year of 2016. An economic census commenced in 2016 with the first phase being a business listing exercise which resulted in the identification of 14,452 establishments SB conducted a business listing exercise to provide the frame for the economic census which underpins the rebasing of the national accounts. SB and the mission developed a detailed workplan to demonstrate the magnitude of rebasing the national accounts. The workplan provided a more realistic (but still very tight) deadline for the completion of the exercise which was presented to management. SB and the mission reviewed the industry and product classifications that had been developed with assistance from the Africa Development Bank. It has been recommended that changes could still be made depending on the data available once compilation commences.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Account; AFDB Consultant; CR; ISCR; SB Management; Botswana